Two dimensional triptycene end-capping and its influence on the self-assembly of quinoxalinophenanthrophenazines [data] - Roß, Lisa; Reitemeier, Julius; Ghalami, Farhad; Zhang, Wen-Shan; Gross, Jürgen H.; Rominger, Frank; Elbert, Sven; Schröder, Rasmus R.; Elstner, Marcus; Mastalerz, Michael (Universität, 2023)
A series of quinoxalinophenanthrophenazines (QPPs) with two-dimensional triptycene end-caps was synthesized from a triphenylene base ortho-diamine. UV/vis spectroscopy suggested the formation of dimers in solution which was further confirmed by MALDI-TIMS-TOF-MS and single crystal X-ray diffraction analysis. By the latter, the dimer formation attributed to short π-interactions and a perfect shape-match in one case.
Gefördert durch: Deutsche Forschungsgemeinschaft: SFB 1249 (TP-A04)
Gesehen am 05.12.2024
Keywords: Forschungsdaten; Datenbank